TNFα Blockade Inhibits Both Initial and Continued Control of Pulmonary Coccidioides - Powell, Daniel A.; Shubitz, Lisa F.; Butkiewicz, Christine D.; Trinh, Hien T.; Donovan, Fariba M.; Frelinger, Jeffrey A.; Galgiani, John N. (Frontiers in Cellular and Infection Microbiology, 2022)
Tumor necrosis factor alpha (TNFα) is a pluripotent cytokine that is important in many infections, though its role in Coccidioides infection remains poorly understood. The need to understand TNFα in Coccidioides infection has increased recently with the widespread use of TNFα inhibitors for a wide variety of autoimmune conditions. Here, we couple the newly developed Coccidioides infection model using strain Cp1038 and C57BL/6 × DBA/2J F1 (B6D2F1) mice. B6D2F1 mice develop long-lasting control of Cp1038. Treatment of B6D2F1 mice with anti-TNFα antibodies permits significant fungal proliferation and death. Additionally, we show that antibody treatment limited to the first 2 weeks of infection was sufficient to induce this same loss of fungal control. Importantly, anti-TNFα antibody treatment initiated after fungal control leads to a loss of host control. These results highlight the importance of TNFα in both the initial control of murine Coccidioides and ongoing suppression of the fungal disease.